RECONSTRUCTION REGIONAL MINIMUM WAGE (UMR) INRENEWAL OF EMPLOYMENT LEGAL REMEDIES BASED INDONESIA THE VALUE JUSTICE PANCASILA - Urip Giyono; Eko Soponyono (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
As a developing country, Indonesia is facing problems of population and employment. The crucial question of which is the low level of wages among workers. Employment issues in Indonesian is regulated in Article 5 (1), Article 20 (2) of Article 27 paragraph (2) of Article 28 and ), Article 33 paragraph (1) Constitution 1945.Goverment set wage the rule Minister of Manpower and Transmigration No. 7 of 2013 about Minimum.In the fact wages, worker more difficult to achieve the Living Needs (KHL) to uncover research Reconstruction Policy concept (Minimum Wage) UMR In Indonesia.Rekonstruksi employment Legal Reform efforts Minimum Wage (UMR) The Justice Value based Pancasila. UMR Based on the values of Al-qur'andan Al-Hadith, In human life, not everyone can work for himself, because of the lack of working capital, so it must be working for someone else. Keywords: Justice, Wages and Rights